Placental and plasma early predictive biomarkers for gestational diabetes mellitus. Issue 4 (14th April 2022) - Wei, Yiling; He, Andong; Huang, Zhengrui; Liu, Jia; Li, Ruiman
Abstract: Purpose: Gestational diabetes mellitus (GDM) is a common disease that can give rise to adverse obstetric outcomes. For successful early intervention, more studies on novel predictive biomarkers for GDM are required. Experimental Design: The protein expression profiles of placental tissue from patients with GDM and normal pregnant women were investigated using data‐independent acquisition proteomics with five biological replicates. Early pregnancy maternal plasma samples from the GDM (n = 79) and control (n = 81) groups were used for further validation of candidate biomarkers. Results: We identified 37 differentially expressed proteins between the two groups. CD109 antigen (CD109) and endosialin (CD248) were identified as hub proteins. In the validation experiments, CD109 expression was lower in the early pregnancy maternal plasma of patients with GDM compared with that in normal pregnant women, and CD248 expression was higher in the GDM group. The area under the curve of CD109, CD248, and their combination as indicators in early pregnancy maternal plasma was 0.681, 0.609, and 0.695, respectively. Conclusions and Clinical Relevance: The present study is the first to obtain preliminary evidence that CD109 and CD248 can predict GDM during early pregnancy, as well as providing proteome‐level insights into this disease's pathological mechanisms.